PECULIARITIES OF STANISLAV VOLUNTARY SPORTS SOCIETIES AFTER THE SECOND WORLD WAR (1945–1967) - Maistruk, V. V.; Piatnychuk, D. V.; Piatnychuk, H. O.; Tsap, I. H. (Rehabilitation and Recreation, 2021)
The article presents the materials of the analytical study of the period of foundation and development of Stanislav’s voluntary sports societies after the Second World War. In our opinion, these historical materials reveal the possibilities of systematizing the knowledge of young people in the field of national-patriotic physical education and sports. Modern socio-economic and political transformations of Ukrainian society, accompanied, among other things, by the decline in living standards, its socio-property stratification, propaganda of cruelty, spirituality, violence have affected the moral norms and values of the younger generation. Young people were unprepared for the changes that are taking place in all spheres of life. Therefore, the main priority of humanitarian policy in Ukraine and an important component of national security should be patriotic education of young people, which will affect their awareness of their identity with their homeland, pride in achieving their people, the need to preserve the uniqueness of culture and protect the interests of their people. Through the prism of scientific research on the development of voluntary public organizations, national- patriotic education acquires the character of systematic and purposeful activity of educational institutions, local governments, civil society organizations, citizens to form a high national and patriotic consciousness, a sense of devotion to their Ukrainian state. Our study is based on the idea of strengthening Ukrainian statehood as a consolidating factor in the development of society, the formation of patriotism and the establishment of national values of youth. An important component of our study is to disseminate information about the achievements of our compatriots and their contribution to the treasury of world civilization, in particular in sports, education, science, coverage of the contribution of indigenous peoples and national minorities of Ukraine and citizens of other states to the struggle for independence. The process of its state formation, national scientific, spiritual and cultural heritage.